Deconstruction Perspectives toward the Characters in Langston Hughes’ Father and Son Short Story - Rasyid, Muhammad Jaini; Zamruddin, Mardliya Pratiwi; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research was concerned with the deconstruction perspective of Colonel Norwood, Bert Lewis, and Coralee Lewis’ characters' meaning in Langston Hughes’ Father and Son short story. The research aimed to describe the characters represented in the story and deconstruct to reveal a new meaning. The researcher used a qualitative research design, and the method used in this research was descriptive. The data in this research were narrations related to the three characters obtained by reading the short story and note-taking the data. The results of this study showed that Colonel Norwood held the binary opposition of superior vs. inferior, bad person vs. good person, powerful vs. powerless, and surrounded vs. lonely, while Bert Lewis and Coralee Lewis held the same binary opposition of inferior vs. superior, good person vs. bad person, but the differences Bert Lewis had the meaning of unloved vs. loved and selfish vs. selfless, while Coralee Lewis held the meaning of ugly vs. beauty. The evidence could be seen by undermining the marginal meaning in the text. Therefore, the text of Father and Son short story displayed the meaning in the text was undecidable because many possibilities by all characters could be replaced by a new meaning.